2016
DOI: 10.1111/1467-954x.12363
|View full text |Cite
|
Sign up to set email alerts
|

The Resources of Ageing? Middle-Aged Gay Men's Accounts of Manchester's Gay Voluntary Organizations

Abstract: Middle-aged men's experiences of gay voluntary organizations (GVOs) are neglected in research. To address this knowledge gap, this article extends Bourdieusian theorizing beyond that deployed by Hakim (2010) and Green (2008) concerning 'erotic capital' to demonstrate how norms in GVOs can facilitate or frustrate mobilization of 'ageing capital' by middle-aged gay men living in Manchester (UK), which has implications for comparable cities within and beyond a UK context. Based on interviews with 22 men aged 39-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…While the participants equated youthful bodies with physical functionality and social worth, they defined old age in terms of physical decline, increasing dependence, and diminished social roles. At the same time, similar to previous studies that have found that growing old entails contradictory emotional reactions to bodily changes and social roles (Bennet et al 2017;Gilleard and Higgs 2018;Laz 2003;Simpson 2016), many of the participants articulated conflicting feelings about their changing physical and social realities. On the one hand, the participants were accepting of the inevitability of age-related bodily changes and death.…”
Section: Discussionsupporting
confidence: 82%
“…While the participants equated youthful bodies with physical functionality and social worth, they defined old age in terms of physical decline, increasing dependence, and diminished social roles. At the same time, similar to previous studies that have found that growing old entails contradictory emotional reactions to bodily changes and social roles (Bennet et al 2017;Gilleard and Higgs 2018;Laz 2003;Simpson 2016), many of the participants articulated conflicting feelings about their changing physical and social realities. On the one hand, the participants were accepting of the inevitability of age-related bodily changes and death.…”
Section: Discussionsupporting
confidence: 82%
“…However, these fears were often exacerbated in the case of older LGBT people through experiences of homophobia, transphobia, heteronormativity, invisibility, and denial of identity described above. Many studies described strong communities and networks of older LGBT people as being important in helping older people to maintain their independence (Wilkens, 2015 ; Simpson, 2016 ; King and Stoneman, 2017 ), and participants included in some studies expressed a wish for some of these networks to become more structured. For example, Owen and Catalan explored HIV-positive gay men and recount one participant's aspiration of: getting into a supportive community.…”
Section: Resultsmentioning
confidence: 99%
“…Manchester in the 1980s was a city directed by a vindictive neo-conservative ideology led by the Police Chief, James Anderton, a devout fundamentalist Christian, who pursued an antagonistic crusade against gay men living in the city. Anderton infamously depicted gay men as culpable victims of a deadly disease, the spread of which threatened the existence of 'normal' heterosexual life (Simpson, 2016). He declared those suffering with the virus were in a 'human cesspool of their own making' (Linton, 2012).…”
Section: Manchester United Kingdommentioning
confidence: 99%